Analyze of Russian Innovation Potential During Transition Process to Circular Economy ("Journal "U". Economy. Management. Finance.", 2020)
The problems of Environmental safety and economic sustainability it is a global issue nowadays. It is impossible to find a way for building circular economy without innovation, effective government policy and environment awareness. The purpose of the article is to analyze the problems of transition Russian economy on the circular economy way and preparation measures for sustainability development.
Keywords: sustainability; circular economy; innovations; environmental safety; rational use of natural resources